Not your typical dragon - Bar-el, Dan; Bowers, Tim (New York : Viking, 2013)
"When Crispin Blaze turns seven, he's expected to breathe fire like all the other dragons. But instead of fire, he breathes a host of unusual things"--Provided by publisher
Ages 3 up
Keywords: Dragons -- Fiction; Individuality -- Fiction; Self-acceptance -- Fiction; Dragons -- Pictorial works -- Juvenile fiction; Individuality -- Pictorial works -- Juvenile fiction; Self-acceptance -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Dragons -- Juvenile fiction; Individuality -- Juvenile fiction; Children's stories -- Pictorial works